Status Conflict in Groups - Bendersky, Corinne; Hays, Nicholas A. (Organization Science, 2012)
We introduce status conflicts—defined as disputes over people's relative status (i.e., respect) positions in their group's social hierarchy—as a key group process that affects task group performance. Using mixed research methods, we qualitatively identify the characteristics of status conflicts, validate a four-item survey scale that distinctly measures status conflict, and investigate the relationship between status conflict and group performance. We determine that status conflict exerts a significant negative main effect, moderates the effects of task conflict on group performance, and hurts performance by undermining information sharing more than other types of conflict do.